Information Gap Technique on Speaking Skill - Ryzka Suharnita; Muhammad Candra; Rona Elfiza (Juliet, 2021)
Speaking is one of the most important skills to be developed in education curriculum in Indonesia. It indicates communicative purposes involving authentic oral interaction material because students do not study the language as a subject but also using it for social communication. The purpose of the study was to investigate whether or not there is significant effect of using Information Gap on students’ speaking skill. The population of this research were tenth grade students at SMK Negeri 4 Tanjungpinang and chose randomly by using cluster sampling. The sample of this research were 30 students of X RPL 3 as the experimental group and X MM 1 as the control group consisted 30 students. This research employed Information Gap in experimental group as the source of ideas to make the students communicate. While in the control group were taught using Rote Learning. The instrument used in the study was oral test. The data were analyzed quantitative using descriptive statistics and inferential statistics. The result showed, There is a significant effect of using Information Gap on students’ speaking skill, as tcount = 2.666 and sig = 0.010 < 0.05 and the mean score of post-test in experimental was higher (74.00) than control group (69.23). It can be concluded there is any effect of using Information Gap Technique on speaking skill at SMK Negeri 4 Tanjungpinang.